Leaves from a diary - Mookerjee,Syama Prasad (Calcutta ; New York : Oxford University Press, 1993)
By an Indian politician and social activist; includes some of his letters in appendices (p. 169-212).
Autobiographical.
Keywords: Mookerjee,Syama Prasad, -- 1901-1953.; Politicians -- India -- Biography